Development of E-Commerce Boarding House Integrated with Spatial Visualization of Leaflets and GeoAI Recommendation Algorithm - Gunawan Tari; Ariani Amri; Deril Alfiance Kaligis; Andi Jumardi; Iin Karmila Putri (P3KM Politeknik Pertanian Negeri Samarinda, 2026)
The difficulty of finding efficient boarding houses, especially for students and lower-income workers in Palopo City, remains a major problem due to limited centralized information. The weakness of existing property e-commerce platforms is the lack of integration between spatial location precision and personalized recommendations. This study aims to develop a web-desktop-based boarding house e-commerce system that addresses this weakness by integrating Leaflet Spatial Visualization technology and the GeoAI Recommendation Algorithm. The system development method used is Agile Development with the Scrum model. The Leaflet.js library is used to interactively present boarding house distribution data on a map of Palopo City, complete with dynamic room availability markers. Meanwhile, the GeoAI recommendation feature is implemented using Content-Based Filtering and Collaborative Filtering algorithms to present a personalized list of accommodations based on the user's search history and location preferences. The result of this study is an integrated boarding house e-commerce platform that can improve the user experience in finding accommodations that meet spatial criteria and facilities. The implementation of this system is expected to accelerate the digitalization of boarding house services in Palopo City and become a model for the development of similar applications in the local property sector.